Composite negative electrode material for aqueous zinc metal battery and preparation method of composite negative electrode material
By adopting a three-layer composite negative electrode material, using the combination of zinc powder, carbon balls and bismuth nanosheets, the problems of electrical contact failure, zinc dendrites growth and hydrogen evolution reaction in aqueous zinc metal batteries are solved, and higher cycles are achieved Performance and Coulomb efficiency.
Patent Information
- Application Number
- CN202411677993.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The negative electrode materials of existing aqueous zinc metal batteries are prone to electrical contact failure, zinc dendrites growth and hydrogen evolution reaction during the electrochemical process, resulting in poor circulation performance.
The composite negative electrode material with a three-layer structure is composed of zinc powder, carbon balls and bismuth nanosheets with egg yolk shell structure, and is prepared by high-temperature heat treatment and liquid phase deposition technology. The structure of this material not only improves the efficient transfer of electrons, but also inhibits the hydrogen evolution reaction and the formation of zinc dendrites.
It effectively inhibits electrical contact loss, zinc dendrites growth and hydrogen evolution reaction, improves the cycling performance and Coulomb efficiency of zinc metal batteries, and promotes the plane deposition of zinc ions.
Smart Images

Figure CN119495731A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aqueous zinc metal batteries and relates to negative electrode materials. Specifically, a composite negative electrode material for an aqueous zinc metal battery and a preparation method thereof are provided. The composite negative electrode material can inhibit hydrogen evolution reaction and induce planar deposition of zinc metal, so as to enhance the cycle performance of the aqueous zinc metal battery. Background Art
[0002] At present, most aqueous zinc metal batteries use commercial zinc foil as the negative electrode material, but the low utilization efficiency of zinc foil and the relatively complex preparation process greatly limit its practical application in industry. In contrast, zinc powder is cost-effective and has excellent processability and adjustability when used as the negative electrode material of aqueous zinc metal batteries. However, compared with zinc foil, the specific surface area of zinc powder is significantly increased, and the solid spherical structure makes the zinc negative electrode more complex and difficult to control during the electrochemical process. In addition, due to the long and uneven stripping time, the zinc powder negative electrode is more prone to electrical contact failure, resulting in the separation of active materials from the electrode, which leads to increased battery polarization and poor coulombic efficiency. Therefore, the development of stable and durable zinc powder-based negative electrode materials is crucial to improve the cycle performance of aqueous zinc metal batteries.
[0003] Unlike the two-dimensional zinc foil anode, the monodispersed three-dimensional zinc powder anode allows for a longer redistribution path for zinc ions, a wider nucleation range, and discontinuous electronic transitions; therefore, the top region of the zinc powder is more prone to uneven deposition, and zinc dendrites accumulate continuously during the electroplating / stripping process, eventually penetrating into the diaphragm, causing internal short circuits and producing "dead zinc"; in addition, the volume shrinkage caused by zinc dissolution during the discharge phase leads to electrical contact failure between the powders. In order to solve these problems, classic conductive materials such as MXene, graphene, and carbon nanotubes are often combined with zinc powder to form a composite zinc anode, which can provide sufficient electrons for the zinc powder anode and inhibit the electrical contact failure and zinc dendrite growth of the electrode material. Although significant progress has been made in the research of composite zinc anodes, the enhanced conductivity of the electrode leads to the easy occurrence of hydrogen evolution reaction between the zinc anode and the electrolyte interface, thereby increasing the potential risk of gas production in aqueous zinc metal batteries. Therefore, it is crucial to develop zinc anode materials that can enhance the conductivity of the material while inhibiting the hydrogen evolution reaction. Summary of the invention
[0004] The purpose of the present invention is to provide a composite negative electrode material for an aqueous zinc metal battery and a preparation method thereof, so as to improve the cycle performance of the aqueous zinc metal battery and promote its commercial application; the present invention constructs a three-layer zinc composite negative electrode, whose unique structure can not only provide a rich continuous interface to promote the efficient transfer of electrons, but also reduce the volume expansion and contraction of zinc metal during repeated electroplating / stripping, thereby effectively inhibiting the electrical contact loss of the zinc negative electrode; in addition, the outer layer of bismuth nanosheets can not only inhibit the hydrogen evolution reaction at the zinc metal / electrolyte interface, but also enhance the transmission of ions in the electrochemical process, and induce the Zn (002) crystal plane to be deposited on the electrode surface. Through this planar deposition mechanism, the formation of zinc dendrites can be effectively inhibited.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A composite negative electrode material for an aqueous zinc metal battery, characterized in that the composite negative electrode material is a three-layer coating structure, consisting of zinc powder, carbon balls, and bismuth nanosheets; the carbon balls are in an egg yolk-shell structure, the zinc powder is coated inside the carbon balls, and the bismuth nanosheets are coated on the surface of the carbon balls.
[0007] Furthermore, the composite negative electrode material has a spherical structure with a diameter of 0.5 μm to 1.5 μm.
[0008] Furthermore, in the composite negative electrode material, the content of zinc powder is 70wt% to 85wt%, the content of carbon balls is 5wt% to 10wt%, and the content of bismuth nanosheets is 5wt% to 20wt%.
[0009] Furthermore, the composite negative electrode material is used as a negative electrode in conventional voltage aqueous zinc metal batteries and high voltage aqueous zinc metal batteries.
[0010] Furthermore, the preparation method of the composite negative electrode material for aqueous zinc metal batteries comprises the following steps:
[0011] The carbon powder with egg yolk-shell structure and the zinc powder are mixed evenly in proportion, and the mixture is subjected to high-temperature heat treatment to obtain a zinc-carbon composite powder material;
[0012] The zinc-carbon composite powder material is immersed in a bismuth nitrate solution in proportion, and a bismuth nanosheet coating is formed on the surface of the zinc-carbon composite powder material by liquid phase deposition to obtain a composite negative electrode material.
[0013] Furthermore, the specific process of heat treatment is:
[0014] The mixture is put into a container and sealed, and the container is placed in an argon atmosphere and heated to 300-600°C at a heating rate of 2-5°C / min, followed by heat treatment for 5-15 hours, and then cooled to obtain a zinc-carbon composite powder material; wherein the mass ratio of carbon powder to zinc powder is 1:20-1:5 or 1:(5-20).
[0015] Furthermore, the specific process of liquid phase deposition is:
[0016] Bismuth nitrate pentahydrate is mixed with ethylene glycol and stirred for 10 to 30 minutes, and then ethanol is added, followed by ultrasonic treatment for 10 to 30 minutes and stirring for 10 to 30 minutes to obtain a uniform solution of bismuth nitrate, wherein the mass ratio of bismuth nitrate, ethylene glycol and ethanol is 1:(5 to 15):(5 to 20); a zinc-carbon composite powder material is immersed in the uniform solution of bismuth nitrate for 5 to 30 minutes to obtain a suspension containing the zinc-carbon-bismuth composite powder material, wherein the mass ratio of the zinc-carbon composite powder material to bismuth nitrate is 1:(0.5 to 2.5); the suspension is centrifuged, washed and dried to obtain a composite negative electrode material.
[0017] Furthermore, the preparation process of carbon powder is:
[0018] Dissolve zinc nitrate, hexamethylenetetramine and potassium citrate in distilled water at a molar ratio of 4:2:1, and stir to obtain a mixed aqueous solution;
[0019] The mixed aqueous solution is heated in a water bath at 60 to 90° C. for 10 to 30 minutes, and then naturally aged at room temperature for 1 to 12 hours to obtain zinc citrate microspheres with yolk-shell structure;
[0020] The zinc citrate microspheres are calcined at 500-900°C for 1-5 hours in an inert atmosphere, the product is stirred in a 0.05-0.5 mol / L KOH solution for 10-60 minutes, and then washed, centrifuged and dried to obtain carbon powder with yolk-shell structure.
[0021] Based on the above technical solution, the beneficial effects of the present invention are:
[0022] The present invention provides a composite negative electrode material for an aqueous zinc metal battery, which creatively constructs a three-layer zinc composite negative electrode, which comprises zinc powder, yolk-shell structured carbon, and bismuth metal nanosheets from the inside to the outside. Firstly, the yolk-shell structured carbon and the zinc powder inside it constitute a zinc-carbon composite material. Compared with the existing commercial zinc powder, the size of the zinc-carbon composite material is greatly reduced, and the conductivity is increased after being prepared into an electrode. Moreover, the yolk-shell structured carbon can buffer the volume change caused by zinc metal electroplating / stripping during the electrode cycle. Secondly, the bismuth metal nanosheets coated on the outside of the zinc-carbon composite material can not only inhibit the hydrogen evolution reaction at the electrolyte / electrode interface, but also can simultaneously induce the directional deposition of zinc metal along the Zn (002) crystal plane to realize a planar zinc deposition method. Based on this, the composite negative electrode material for aqueous zinc metal batteries proposed in the present invention can effectively inhibit electrical contact loss, zinc dendrite growth, side reactions and hydrogen evolution reactions occurring inside the battery during the electrochemical reaction; wherein the zinc-carbon composite material can induce the generation of a material with a lower zinc ion diffusion barrier and accelerate the transport of zinc ions at the electrode / electrolyte interface, thereby causing the deposited zinc metal to be mainly distributed inside the yolk shell carbon spheres; the bismuth metal nanosheets coated on the outer layer have a high Gibbs free energy, can inhibit the hydrogen evolution reaction of the zinc-carbon composite material, and can also induce a portion of the zinc metal to be uniformly deposited on the bismuth surface.
[0023] In summary, the present invention combines high-temperature zinc infiltration and room-temperature liquid phase reduction strategies to synthesize a zinc-carbon-bismuth composite microsphere material with a three-layer structure, effectively constructing an ideal zinc metal battery negative electrode material with ideal high electron / ion transmission capacity, low resistivity and high Young's modulus, and exerting an ideal synergistic effect; finally, the composite negative electrode material for aqueous zinc metal batteries in the present invention has a high conductivity at 1 mA / cm 2 At current densities of 0.5 mAh / cm 2 The overpotential below 35mV was achieved at a surface capacity of 1.5477 W / m, providing a new perspective for the study of stable metal zinc / electrolyte interface. Furthermore, a high-performance zinc metal secondary battery was successfully obtained by using high-areal capacity CNT@MnO2 as the positive electrode, 3mol / L ZnSO4+0.2mol / L MnSO4 electrolyte as the electrolyte, and matching it with a composite negative electrode material for zinc metal batteries.
[0024] In addition, the preparation process of the zinc-carbon-bismuth composite negative electrode material for aqueous zinc metal batteries in the present invention is novel and simple, and has the advantages of low cost and good synthesis consistency. It is essentially different from the preparation process of similar zinc negative electrodes in the prior art. Moreover, the prepared composite negative electrode material can not only reduce the volume expansion and contraction of zinc metal during repeated electroplating / stripping, but also reduce the transmission barrier of zinc ions at the electrolysis interface and inhibit the hydrogen evolution reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a comparison diagram of the structure and working principle of the composite negative electrode material for aqueous zinc metal batteries in the present invention and the traditional zinc powder negative electrode.
[0026] Figure 2 These are SEM and TEM images of the composite negative electrode material for aqueous zinc metal batteries in Example 1 of the present invention.
[0027] Figure 3 The zinc metal symmetric battery in Example 1 of the present invention and Comparative Example 1 at 5 mA / cm 2 SEM morphology after electroplating for 80 min at a current density of .
[0028] Figure 4 The zinc metal symmetric battery in Example 1 of the present invention and Comparative Example 1 at 1 mA / cm 2 The current density is 0.5 mAh / cm 2 Cyclic performance diagram under surface capacity.
[0029] Figure 5 The zinc metal symmetric battery in Example 2 of the present invention and Comparative Example 2 at 1 mA / cm 2 The current density is 1 mAh / cm 2 Overpotential diagram under surface capacity.
[0030] Figure 6 It is a comparison diagram of the hydrogen evolution reaction in 3 mol / L ZnSO4 electrolyte using a three-electrode test system in Example 2 of the present invention and Comparative Example 2.
[0031] Figure 7 It is a cycle performance diagram of the aqueous zinc metal battery (zinc-carbon-bismuth composite negative electrode / CNT@MnO2 positive electrode) in Example 3 of the present invention and Comparative Example 3. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and technical effect of the present invention clearer and more complete, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0033] Example 1
[0034] This embodiment provides a composite negative electrode material for an aqueous zinc metal battery and a preparation method thereof. The composite negative electrode material is Figure 1 As shown, a three-layer coating structure consisting of zinc powder, carbon balls and bismuth nanosheets is adopted. The carbon balls are in an egg yolk shell structure, the zinc powder is coated inside the carbon balls, and the bismuth nanosheets are coated on the surface of the carbon balls.
[0035] The composite negative electrode material for aqueous zinc metal batteries is prepared by the following steps:
[0036] Dissolve 0.48 mmol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 0.26 mmol of hexamethylenetetramine ((CH2)6N4) and 0.13 mmol of potassium citrate monohydrate (K3C6H5O7·H2O) in 50 mL of distilled water and stir well;
[0037] The mixed aqueous solution was heated in a water bath at 90°C for 20 minutes and then aged naturally at room temperature. As the aging time increased, the growth of the shell and the shrinkage of the core continued. When the aging time increased to 8 hours, the core disappeared, leaving zinc citrate microspheres with a spherical yolk-shell structure.
[0038] The spherical yolk-shell structured zinc citrate microspheres were calcined at 800°C for 2 hours in an argon / hydrogen (9:1) atmosphere, and the product was placed in a 0.1 mol / L KOH solution and stirred for 20 minutes to remove excess zinc oxide, and then washed, centrifuged and dried to obtain a carbon powder material;
[0039] After 5 g of carbon powder and 25 g of zinc powder were ground and mixed for 3 hours, the mixture was placed in a ceramic container and sealed, and heated to 500° C. at a heating rate of 5° C. / min in an argon atmosphere and then heat treated for 12 hours to obtain a zinc-carbon composite powder material;
[0040] A mixed solution of 3 mmol of bismuth nitrate pentahydrate (Bi(NO3)2·5H2O) and 20 mL of ethylene glycol was magnetically stirred for 30 minutes, and then 40 mL of ethanol was added and ultrasonically treated for 30 minutes, and then stirred for 30 minutes to obtain a uniform solution; 10 g of zinc-carbon composite powder was immersed in the uniform solution for 5 minutes, and zinc atoms reduced bismuth ions to bismuth metal element at room temperature to form bismuth metal nanosheets, thereby forming a black coating of bismuth metal nanosheets on the surface of the zinc-carbon composite powder material, and a suspension containing zinc-carbon-bismuth composite powder material was obtained;
[0041] Finally, the obtained suspension containing zinc-carbon-bismuth composite powder material is centrifuged, washed and dried to obtain the zinc-carbon-bismuth composite powder material, which is the composite negative electrode material for the aqueous zinc metal battery.
[0042] In order to test the electrochemical performance of the composite negative electrode material for aqueous zinc metal batteries, a zinc metal symmetric battery was constructed based on the composite negative electrode material, with the electrodes on both sides mainly composed of zinc-carbon-bismuth composite materials, and the electrolyte consisting of zinc sulfate and a solvent (3 mol / L zinc sulfate electrolyte was prepared by constant volume of ZnSO4·7H2O and distilled water);
[0043] At the same time, this embodiment also provides a comparative example 1: the electrodes on both sides are commercial pure zinc powder, matched with the same concentration of zinc sulfate electrolyte, and assembled under the same process as this embodiment to obtain a zinc metal symmetrical battery.
[0044] Example 2
[0045] This embodiment provides a three-electrode test system, wherein the working electrode, the counter electrode and the reference electrode are respectively the zinc-carbon-bismuth composite negative electrode material prepared in Example 1, a commercial platinum sheet and Ag / AgCl, and the electrolyte is the same as that in Example 1;
[0046] At the same time, this embodiment also provides a comparative example 2: the working electrode is replaced with a pure zinc material or the zinc-carbon composite material prepared in Example 1, and the other conditions remain unchanged, and the hydrogen evolution reaction is tested under the same process as this embodiment.
[0047] Example 3
[0048] This embodiment provides an aqueous zinc metal battery, wherein the positive electrode is a CNT@MnO2 positive electrode sheet, the negative electrode is a zinc-carbon-bismuth composite negative electrode material prepared in Example 1, and the electrolyte is 3 mol / L ZnSO4+0.2 mol / L MnSO4;
[0049] At the same time, this embodiment also provides comparative example 3: the positive electrode is a CNT@MnO2 positive electrode sheet, the negative electrode is commercial pure zinc powder, and the same electrolyte as that of this embodiment is matched, and an aqueous zinc metal battery is assembled under the same process as the embodiment.
[0050] The beneficial effects of the present invention are described in detail below in combination with the working principle and test results.
[0051] like Figure 1 The figure shows the physical and chemical properties of the composite negative electrode material for aqueous zinc metal batteries and commercial pure zinc powder materials in the present invention and the schematic diagram of the negative electrode surface morphology after battery cycling; it can be seen from the figure that due to the long and uneven stripping time of the battery negative electrode, the pure zinc powder is prone to uncontrolled electrical contact loss, which leads to the separation of the active material from the electrode, thereby increasing the battery polarization and deteriorating the Coulomb efficiency; in addition, due to the low Young's modulus, high ion transport barrier and susceptibility to corrosion by aqueous electrolytes of the pure zinc powder negative electrode, the pure zinc powder negative electrode is prone to dendrite growth, hydrogen evolution reaction and heterogeneous metal deposition during the battery cycle. Compared with the pure zinc powder negative electrode, the zinc-carbon-bismuth composite negative electrode with a three-layer coating structure provided by the present invention can provide high conductivity, firm electrical contact, and enhanced Gibbs free energy, which can effectively inhibit hydrogen evolution reaction and adjust the reversibility of metal deposition; and it also has a low ion transport barrier, which can induce the preferential deposition of the Zn (002) crystal plane, thereby achieving the planar deposition of zinc metal to achieve the purpose of inhibiting zinc dendrites. It can be seen that the present invention combines high-temperature zinc infiltration and room-temperature liquid phase reduction strategies to synthesize a zinc-carbon-bismuth composite microsphere material with a three-layer coating structure, effectively constructing an ideal zinc metal battery negative electrode material with ideal high electron / ion transmission capability, low resistivity and high Young's modulus, and exerting an ideal synergistic effect.
[0052] like Figure 2 The SEM and TEM images of the zinc-carbon-bismuth composite negative electrode material prepared in Example 1 are shown. It can be seen from the figure that the prepared zinc-carbon-bismuth composite material is a spherical structure with a diameter of about 0.5 to 1.5 μm. Figure 2 As shown in (a), bismuth metal nanosheets are coated on the surface of zinc-carbon microspheres. Figure 2 As shown in (b) and (c).
[0053] like Figure 3 The results are shown for the zinc symmetric battery in Example 1 and Comparative Example 1 at 5 mA / cm 2 The SEM morphology images after electroplating for 20 min and 80 min at a current density of , it can be seen from the figure that the zinc deposition corresponding to Comparative Example 1 shows obvious zinc dendrite growth and uneven zinc deposition and the zinc deposition layer is not dense, while the zinc deposition corresponding to Example 1 has no obvious zinc dendrites and the zinc deposition is dense and uniform, indicating that the zinc-carbon-bismuth composite negative electrode in the present invention can effectively induce zinc metal to deposit along the Zn (002) crystal plane, thereby achieving planar deposition and inhibiting the growth of zinc dendrites.
[0054] like Figure 4 The figure shows the zinc metal symmetric battery in Example 1 and Comparative Example 1 at 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cycle performance diagram under the surface capacity of , it can be seen from the figure that comparative example 1 experienced serious side reactions, and the polarization voltage increased sharply after 4 hours; while Example 1 showed excellent cycle stability and the side reactions were significantly suppressed. After 60 hours, it was still able to provide stable cycle and the polarization voltage value remained basically unchanged, indicating that the zinc-carbon-bismuth composite negative electrode in the present invention can significantly suppress the electrical contact loss of the electrode and the side reactions between the electrode / electrolyte interface.
[0055] like Figure 5 The results are shown in Example 1 and Comparative Example 1 for the zinc metal symmetric battery at 1 mA / cm 2 The current density is 1 mAh / cm 2 The overpotential diagram under the surface capacity shows that the overpotential of pure zinc negative electrode and zinc-carbon composite negative electrode are higher than that of zinc-carbon-bismuth composite electrode. This is mainly due to the high electrical conductivity provided by the composite carbon material and the low ion transport barrier provided by the bismuth metal nanosheets, which leads to the inhibition of the interfacial side reactions of the battery and the promotion of rapid ion dynamics.
[0056] like Figure 6The figure shows the hydrogen evolution capacity of the three electrodes in the three-electrode test system in Example 2 and Comparative Example 2. It can be seen from the figure that the zinc-carbon composite negative electrode is most likely to undergo hydrogen evolution reaction, followed by the pure zinc negative electrode and the zinc-carbon-bismuth composite negative electrode. This is mainly because the increase in the conductivity and specific surface area of the zinc-carbon composite electrode promotes the hydrogen evolution reaction at the negative electrode interface. After the bismuth metal nanosheets are coated on the outer layer of the zinc-carbon composite material, they can inhibit the hydrogen evolution reaction of the zinc-carbon composite material due to their high Gibbs free energy.
[0057] like Figure 7 The results show that the aqueous zinc metal battery (zinc-carbon-bismuth composite negative electrode / CNT@MnO2 positive electrode) in Example 3 and Comparative Example 3 is stable at 0.2A g -1 The current density and cycle performance diagram under 25°C environment show that comparative example 3 shows poor cycle stability and the battery fails after 54 cycles, while example 3 shows more excellent cycle stability and the capacity retention rate is as high as 97% after 100 cycles, indicating that the zinc-carbon-bismuth composite negative electrode material with a three-layer coating structure in the present invention has extremely strong practical value.
[0058] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.
Claims
1. A composite negative electrode material for an aqueous zinc metal battery, characterized in that: The composite negative electrode material is a three-layer coating structure, consisting of zinc powder, carbon balls, and bismuth nanosheets; the carbon balls are in an egg yolk shell structure, the zinc powder is coated inside the carbon balls, and the bismuth nanosheets are coated on the surface of the carbon balls.
2. The composite negative electrode material for aqueous zinc metal batteries according to claim 1, characterized in that: The composite negative electrode material is in a spherical structure with a diameter of 0.5 μm to 1.5 μm.
3. The composite negative electrode material for aqueous zinc metal batteries according to claim 1, characterized in that: In the composite negative electrode material, the content of zinc powder is 70wt% to 85wt%, the content of carbon balls is 5wt% to 10wt%, and the content of bismuth nanosheets is 5wt% to 20wt%.
4. The composite negative electrode material for aqueous zinc metal batteries according to claim 1, characterized in that: The composite negative electrode material is used as a negative electrode in conventional voltage aqueous zinc metal batteries and high voltage aqueous zinc metal batteries.
5. The method for preparing a composite negative electrode material for an aqueous zinc metal battery according to claim 1, characterized in that: The following steps are involved: The carbon powder with egg yolk-shell structure and the zinc powder are mixed evenly in proportion, and the mixture is subjected to high-temperature heat treatment to obtain a zinc-carbon composite powder material; The zinc-carbon composite powder material is immersed in a bismuth nitrate solution in proportion, and a bismuth nanosheet coating is formed on the surface of the zinc-carbon composite powder material by liquid phase deposition to obtain a composite negative electrode material.
6. The method for preparing a composite negative electrode material for an aqueous zinc metal battery according to claim 5, characterized in that: The specific process of heat treatment is: The mixture is put into a container and sealed, and the container is placed in an argon atmosphere and heated to 300-600°C at a heating rate of 2-5°C / min, followed by heat treatment for 5-15 hours, and then cooled to obtain a zinc-carbon composite powder material; wherein the mass ratio of carbon powder to zinc powder is 1:(5-20).
7. The method for preparing a composite negative electrode material for an aqueous zinc metal battery according to claim 5, characterized in that: The specific process of liquid deposition is: Bismuth nitrate pentahydrate is mixed with ethylene glycol and stirred for 10 to 30 minutes, and then ethanol is added, followed by ultrasonic treatment for 10 to 30 minutes and stirring for 10 to 30 minutes to obtain a uniform solution of bismuth nitrate, wherein the mass ratio of bismuth nitrate, ethylene glycol and ethanol is 1:(5 to 15):(5 to 20); a zinc-carbon composite powder material is immersed in the uniform solution of bismuth nitrate for 5 to 30 minutes to obtain a suspension containing the zinc-carbon-bismuth composite powder material, wherein the mass ratio of the zinc-carbon composite powder material to bismuth nitrate is 1:(0.5 to 2.5); the suspension is centrifuged, washed and dried to obtain a composite negative electrode material.
8. The method for preparing a composite negative electrode material for an aqueous zinc metal battery according to claim 5, characterized in that: The preparation process of carbon powder is: Dissolve zinc nitrate, hexamethylenetetramine and potassium citrate in distilled water at a molar ratio of 4:2:1, and stir to obtain a mixed aqueous solution; The mixed aqueous solution is heated in a water bath at 60 to 90° C. for 10 to 30 minutes, and then naturally aged at room temperature for 1 to 12 hours to obtain zinc citrate microspheres with yolk-shell structure; The zinc citrate microspheres are calcined at 500-900°C for 1-5 hours in an inert atmosphere, the product is stirred in a 0.05-0.5 mol / L KOH solution for 10-60 minutes, and then washed, centrifuged and dried to obtain carbon powder with yolk-shell structure.
Citation Information
Patent Citations
Negative material for zinc-nickel battery and method for preparing same
CN101841034A
Method for preparing three-dimensional porous microsphere defined by nitrogen / sulfur co-doped carbon nanosheet with embedded metal / carbon yolk shell structure
CN110247030A
Zinc-cobalt sulfide / carbon nano negative electrode material and preparation method thereof
CN111293300A
Negative electrode composite material for zinc secondary battery as well as preparation method and application of negative electrode composite material
CN115548316A
Bi-MOF (at) rGO material as well as preparation method and application thereof
CN115732684A
Cited By
Composite zinc powder negative electrode material for aqueous zinc ion battery as well as preparation method and application of composite zinc powder negative electrode material
CN122417827A